Comprehensive RNA-Seq Analysis of Potential Therapeutic Targets of Gan–Dou–Fu–Mu Decoction for Treatment of Wilson Disease Using a Toxic Milk Mouse Model - Wei, Taohua; Hao, Wenjie; Tang, Lulu; Wu, Huan; Huang, Shi; Yang, Yue; Qian, Nannan; Liu, Jie; Yang, Wenming; Duan, Xianchun (Frontiers in Pharmacology, 2021)
Background: Gan-Dou-Fu-Mu decoction (GDFMD), whch has proven can improves liver fibrosis in experimental and clinical studies including toxic mouse model of Wilson Disease (Model). However, the mechanisms underlying the effect of GDFMD have not been characterized. Herein, we deciphered the potential therapeutic targets of GDFMD using mRNA transcriptome analysis. Methods: We identified differentially expressed genes (DEGs) that were upregulated in the Model (Model vs. control) and those that were downregulated upon treatment with GDFMD (compared to the Model) using RNA-sequencing (RNA-seq). Biological functions and signaling pathways in which the DEGs were involved were determined by gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway analyses. A protein–protein interaction network was constructed using the STRING database, and the modules were identified using the MCODE plugin with the Cytoscape software. Several of the genes identified by RNA-seq analysis were validated by real-time quantitative PCR. Results: 2124 DEGs were screened out according to the two comparisons (Model vs. control and Model vs. GDFMD), and dozens of GO and KEGG pathways terms that could be modulated by GDFMD were identified. Dozens of pathways involved in metabolism (including metabolic processes for organic acids, carboxylic acids, monocarboxylic acids, lipids, fatty acids, cellular lipids, steroids, alcohols, eicosanoids, long-chain fatty acids), immune and inflammatory response (such as complement and coagulation cascades, cytokine–cytokine receptor interaction, inflammatory mediator regulation of TRP channels, antigen processing and presentation, T-cell receptor signaling pathway), and liver fibrosis (such as ECM-receptor interactions) were found to be potential therapeutic targets of GDFMD in the Model. Some hub genes and four modules were identified in the PPI network. The results of real-time quantitative PCR analysis were consistent with those of RNA-seq analysis. Conclusion: We performed gene expression profiling of GDFMD-treated WD model mice using RNA-seq analysis and found the genes, pathways, and processes effected by the treatment. Our study provides a theoretical basis to prevent liver fibrosis resulting from Wilson disease using GDFMD.